Legal Protection of Consumer Rights in Transactions at TikTok Shop: Unraveling New Legal Insights - Sarah Septyaningsih; Mochammad Tanzil Multazam; Bobur Sobirov (Kosmik Hukum, 2023)
Tiktok is one of the choices for social media that has many users today. The use of the Tiktok Shop feature is able to increase consumer interest with practical reasons for purchasing, with an easy payment system and a faster time spent. The purpose of this research is to find out the legal rights and obligations of product owners in transactions at the Tiktok Shop, the legal rights and obligations of consumers in international social media marketplace transactions, to know the laws governing the protection of intellectual property rights and consumers in transactions at the Tiktok Shop, to find out legal issues which often appear in transactions at the Tiktok Shop related to Intellectual Property Rights and consumer protection. The research method used is normative juridical. The results and suggestions of this study explain that consumers and owners of capital must both have their rights protected, especially consumers who are the most vulnerable in transactions at the Tiktok Shop. The need for good faith and implementation of obligations from both parties so that there is no conflict during transactions. Various forms of action taken by consumers and product owners themselves without good faith, means that they are not included in online buying and selling transactions because they are not bona fide.Keywords: Legal Protection, consumer rights, product owner, tiktok shop